2008
DOI: 10.1021/es071370r
|View full text |Cite
|
Sign up to set email alerts
|

XANES−EXAFS Analysis of Se Solid-Phase Reaction Products Formed upon Contacting Se(IV) with FeS2and FeS

Abstract: The solid-phase Se speciation after short-term (3 weeks) contact of selenite [Se(IV)] oxyanions with pyrite (FeS2) and troilite (FeS) was investigated using X-ray absorption spectroscopy (XAS; X-ray absorption near-edge spectroscopy-extended X-ray absorption fine structure (XANES-EXAFS)). It was found that the nature of the sulfide mineral dictates the final speciation since respectively Se(0) and FeSe(x) were formed, meaning that the reaction mechanism is different and that these phases cannot be regarded as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 40 publications
9
64
1
Order By: Relevance
“…In contrast, some studies have strongly suggested that Se(IV) can be reduced by Fe(II) included in green rust [28], magnetite, mackinawite and siderite [29], pyrite [30], and troilite [31]. In this study, the great decrease of selenium concentration by a small amount of addition of freshly synthesized magnetite even in the silicate solution, unlike commercial magnetite, suggests the change of selenite oxidation state.…”
Section: Behaviors Of Selenium Ions In Solution Contained Iron and Ircontrasting
confidence: 56%
“…In contrast, some studies have strongly suggested that Se(IV) can be reduced by Fe(II) included in green rust [28], magnetite, mackinawite and siderite [29], pyrite [30], and troilite [31]. In this study, the great decrease of selenium concentration by a small amount of addition of freshly synthesized magnetite even in the silicate solution, unlike commercial magnetite, suggests the change of selenite oxidation state.…”
Section: Behaviors Of Selenium Ions In Solution Contained Iron and Ircontrasting
confidence: 56%
“…This can kinetically inhibit the dissolution required for the further transformation into more stable species (FeSe 2 ), leading the system to undergo redox disequilibrium in short-term laboratory experiments. This may be one of the reasons why in this study, even after the depletion of the aqueous Se(IV) at pH 5.65, only Se(0) is observed, in line with previous works (Breynaert et al, 2008(Breynaert et al, , 2010. A previous study on more reactive nano-sized pyrite/greigite mixture revealed the formation of a large amount of FeSe 2 , confirming the critical effect of reaction kinetics on the reaction products (Charlet et al, 2012).…”
Section: Thermodynamic Calculationssupporting
confidence: 92%
“…For example, Breynaert et al (2008) found crystalline Se(0) as the only Se-bearing reaction product of the pyrite-Se(IV) reaction between pH 6.5 and 8.5. Elemental Se was also observed as the reaction product of pyrite-HSe À reaction at pH 6.6 (Liu et al, 2008), and Se(IV)-doped pyrite at pH values ranging from 3.7 to 5.0 (Diener et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…18−20 Framboids are difficult to synthesize in the laboratory, 39 and no experimental evidence on Se-framboidal interactions is available. Some experimental studies used iron sulfides (e.g., mackinawite, 42 pyrite [18][19][20]43 ) and sorbed Se onto them. When synthetic pyrite was used, the Se was coreduced leading to the formation of ferroselite FeSe(-I) x .…”
Section: Environmental Science and Technologymentioning
confidence: 99%